Intrinsic work motivation and pension reform preferences - Heinemann, Friedrich; Hennighausen, Tanja; Moessinger, Marc-Daniel (Journal of pension economics and finance, 2013)
Although demographic change leaves pay-as-you-go pension systems unsustainable, reforms, such as a higher pension age, are highly unpopular. This contribution looks into the role of intrinsic motivation as a driver for pension reform preferences. Theoretical reasoning suggests that this driver should be relevant as it decreases the subjective costs of a higher pension age. We test this key hypothesis on the basis of the German General Social Survey (ALLBUS). The results are unambiguous: in addition to factors such as age or education, the inclusion of intrinsic work motivation helps improving our prediction of an individual's reform orientation.
First published online 11 October 2012
Gesehen am 15.09.2021